2019
DOI: 10.1101/797076
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sporulation environment drives phenotypic variation in the pathogenAspergillus fumigatus

Abstract: 8Aspergillus fumigatus causes more than 300,000 life-threatening infections annually and is widespread across 9 varied environments with a single colony producing thousands of conidia, genetically-identical dormant spores. 10 Conidia are easily wind-dispersed to new environments where they can germinate and, if inhaled by susceptible 11 hosts, cause disease. Using high-throughput, single-cell analysis we show that germination phenotypes vary 12 among genetically-identical individuals and that the environ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…9). Our data suggest that conidia prepare for the sensed environment, in agreement with previous studies (Earl Kang et al, 2021;Hagiwara et al, 2017;Krach et al, 2022). Interestingly, conidia begin to express genes and store mRNA needed for subsequent growth in the sensed environment even before detachment from the conidiophore or dormancy (Wang et al, 2021).…”
Section: Dormancy Breaking and Epigenetic Regulation Of Lifestyle Shi...supporting
confidence: 91%
“…9). Our data suggest that conidia prepare for the sensed environment, in agreement with previous studies (Earl Kang et al, 2021;Hagiwara et al, 2017;Krach et al, 2022). Interestingly, conidia begin to express genes and store mRNA needed for subsequent growth in the sensed environment even before detachment from the conidiophore or dormancy (Wang et al, 2021).…”
Section: Dormancy Breaking and Epigenetic Regulation Of Lifestyle Shi...supporting
confidence: 91%
“…As published in our previous studies, the dynamic surfome of A. fumigatus is affected by various cultivation conditions, including the medium, temperature, and time, and contains many proteins secreted by nonclassical pathways ( 10 , 11 ). Correspondingly, a recent study also revealed that the phenotypes of A. fumigatus germinating conidia vary among genetically identical conidia ( 66 ). Here, we detected 61, 69, and 85 proteins on dormant, swollen, and germinating conidia, respectively; while 136 proteins were found on the surface of hyphae ( Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, experimental conditions of both studies were different, such as the pre-culture medium and germination medium. Nutritional environment during sporulation, as well as during germination, affects the rate of the breaking of dormancy and growth in A. fumigatus [85]. A. fumigatus strains were cultivated on Sabouraud agar slants (dextrose 40 g/L, peptone 10 g/L, agar 20 g/L, pH = 5.6) for five days at 30 • C, and A. niger was cultivated on complete medium (CM) (1.5% agar, 6.0 g NaNO3, 1.5 g KH2PO4, 0.5 g KCl, 0.5 g MgSO4, 4.5 g D-glucose, 0.5% casamino acids, 1% yeast extract, and 200 µL trace elements per liter) for 12 days at 25 • C. RNA was extracted after growth in liquid RPMI 1640 (Gibco ® life technologies) and liquid CM for A. fumigatus and A. niger, respectively.…”
Section: Discussionmentioning
confidence: 99%